Strengthening Marketing Communication in Socializing to SMEs in Pekanbaru City - Lani, Oktri Permata; Razali, Geofakta (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
A product will not be known to potential consumers if there is no effort to inform them about it. Through the communication process, companies have the opportunity to introduce, inform, and spread news about the products they offer to potential consumers. Marketing communication encompasses various multidisciplinary approaches that combine theories and concepts from communication and marketing sciences. The role of small and medium-sized enterprises (SMEs) is of significant importance in the effort to develop the economic well-being of society. This is particularly related to the effort to empower the community economically and the number of jobs that can be created by these enterprises. In addition to having strategic importance in the development process, SMEs also serve as a tool for achieving a more equitable distribution of the development outcomes achieved so far. The research method uses Participatory Action Research (PAR) with socialization assistance to several SMEs in the city of Pekanbaru.